Late Onset Dipeptidyl Peptidase -4 Inhibitor Associated Seronegative Rheumatoid Arthritis - Vaidya, Binit; Adhikari, Bhojraj; Bhochhibhoya, Manisha; Nakarmi, Shweta (Journal of Nepal Health Research Council, 2021)
Drug-induced arthritis is not an uncommon scenario. DPP-4 inhibitors could potentially cause adverse-events mediated by cytokine-induced inflammation leading to arthritis. The activity of the DPP-4 enzyme could be inversely related to the development of rheumatoid arthritis, explaining the increased inflammatory activity with its inhibition by a drug. We discuss a 72-year-old gentleman with twenty-three years of history of type 2 diabetes mellitus, who after 6 years of treatment with a DPP-4 inhibitor, developed features of inflammatory arthritis and fulfilled the criteria for seronegative rheumatoid; which eventually subsided after stopping the drug. Keywords: DDP-4 inhibitor; diabetes mellitus; Nepal; rheumatoid arthritis; seronegative